An interpretable diagnosis of retinal diseases using vision transformer and Grad-CAM - Bhuiyan, Mahdi Hasan; Haldar, Sumit; Chowdhury, Maisha Shabnam; Bushra, Nazifa; Jilan, Tahsin Zaman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.